Effects of Arbuscular Mycorrhizal Fungi on Watermelon Growth, Elemental Uptake, Antioxidant, and Photosystem II Activities and Stress-Response Gene Expressions Under Salinity-Alkalinity Stresses - Ye, Lin; Zhao, Xia; Bao, Encai; Cao, Kai; Zou, Zhirong (Frontiers in Plant Science, 2019)
Salinity-alkalinity stress has caused severe environment problems that negatively impact the growth and development of watermelon (Citrullus lanatus L.). In this study, watermelon seedlings were inoculated with the arbuscular mycorrhizal fungi (AMF) Funneliformis mosseae to investigate its effect on watermelon growth and development. The main measurements included morphological traits, elemental and water uptake, the level of reactive oxygen species, antioxidant enzyme and photosynthesis activities, and relative expression levels of stress response genes. Under salinity-alkalinity stresses, watermelon morphological traits, elemental and water uptake were all significantly alleviated after incubation with AMF. Antioxidant abilities of watermelon were significantly improved after incubation with AMF in salinity-alkalinity stresses. Under normal conditions, all photosynthesis related parameters were significantly increased after incubation of AMF. In contrast, they were all significantly reduced under salinity-alkalinity stresses and were all significantly alleviated after incubation of AMF. Salinity-alkalinity stresses impacted the chloroplast structure and AMF significantly alleviated these damages. Under salinity-alkalinity stresses, the relative expression level of RBCL was significantly reduced and was significantly alleviated after AMF treatment. The relative expression level of PPH was significantly increased and was further significantly reduced after AMF treatment. For the relative expression levels of antioxidant response related genes Cu-Zn SOD, CAT, APX, GR, their relative expression levels were significantly increased and were further significantly increased after AMF treatment. Our study demonstrated the beneficial effects of AMF under salinity-alkalinity stresses, which could be implicated in the management of watermelon cultivation under salinity-alkalinity regions.